AN ESTIMATION OP HEAT CHANGES IN THE BAY OF BENGAL OFF VISAKHAPATNAM - Ramasastry, A A (Indian Journal of Fisheries, 2016)
Heat changes in the upper layers of the sea result from a number of factors which might be conveniently divided into two groups. They are (1) the energy transfer processes and (2) the advective processes. Over limited areas and time intervals the heat budget of the oceans has been studied previously by a number of scientists and thus the factors that change the temperature are fairly well known and are listed in detail by Severdrup etal. (1942) and LaFond (1954).